Pengaruh Corporate Social Responsibility Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Corporate Governance Sebagai Variabel Moderating Pada Perusahaan Perbankan Yang Terdaftar Di BEI - Nurul Hikmah; Maya Sari; Irfan (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to analyze the effect of corporate social responsibility and company size on company value with corporate governance as a moderate variable in banking companies listed on the IDX for the 2016-2021 period. The type of approach in this study is quantitative associative by collecting data using secondary data in the form of an annual report published by the company on the official website of the IDX, www.idx.co.id. The study population is all banking companies on the IDX for the period 2016-2021. The sampling technique with purposive sampling obtained samples from 14 companies with the observation year starting from 2016-2021 so that 84 samples were obtained. The data analysis technique used in this study used moderated regression analysis (MRA) with the Statistical Program for Social Science (SPSS 20) tool. The results of this study show that corporate social responsibility affects company value. the size of the company affects the value of the company. Corporate governance is able to moderate the influence of corporate social responsibility on company values. Corporate governance is able to moderate the influence of company size on company value.